Centralized design and production of the ultra-high vacuum and laser-stabilization systems for the AION ultra-cold strontium laboratories - Stray,B; Ennis,O; Hedges,S; Dey,S; Langlois,M; Bongs,K; Lellouch,S; Holynski,M; Bostwick,B; Chen,J; Eyler,Z; Gibson,V; et al. (AVS Quantum Science, 2024)
This paper outlines the centralized design and production of the ultra-high-vacuum sidearm and laser-stabilization systems for the AION Ultra-Cold Strontium Laboratories. Commissioning data on the residual gas and steady-state pressures in the sidearm chambers, on magnetic field quality, on laser stabilization, and on the loading rate for the 3D magneto-optical trap are presented. Streamlining the design and production of the sidearm and laser stabilization systems enabled the AION Collaboration to build and equip in parallel five state-of-the-art Ultra-Cold Strontium Laboratories within 24 months by leveraging key expertise in the collaboration. This approach could serve as a model for the development and construction of other cold atom experiments, such as atomic clock experiments and neutral atom quantum computing systems, by establishing dedicated design and production units at national laboratories.